2010
DOI: 10.1371/journal.pone.0014279
|View full text |Cite
|
Sign up to set email alerts
|

Does Collocation Inform the Impact of Collaboration?

Abstract: BackgroundIt has been shown that large interdisciplinary teams working across geography are more likely to be impactful. We asked whether the physical proximity of collaborators remained a strong predictor of the scientific impact of their research as measured by citations of the resulting publications.Methodology/Principal FindingsArticles published by Harvard investigators from 1993 to 2003 with at least two authors were identified in the domain of biomedical science. Each collaboration was geocoded to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 7 publications
1
44
1
2
Order By: Relevance
“…Both crossdiscipline and cross-site collaborations contributed to this growth. Importantly, the analysis here suggests that multi-site team science initiatives are more likely to foster greater collaboration and cooperation when they are designed to be transdisciplinary from the start, whereas one previous study [24] found that across all types of biomedical studies increasing physical distance between investigators is a major deterrent to scientific impact. In the current environment of shrinking grant support, funding agencies may want to consider focusing on transdisciplinary team science as a way to increase research success for a given level of funding.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Both crossdiscipline and cross-site collaborations contributed to this growth. Importantly, the analysis here suggests that multi-site team science initiatives are more likely to foster greater collaboration and cooperation when they are designed to be transdisciplinary from the start, whereas one previous study [24] found that across all types of biomedical studies increasing physical distance between investigators is a major deterrent to scientific impact. In the current environment of shrinking grant support, funding agencies may want to consider focusing on transdisciplinary team science as a way to increase research success for a given level of funding.…”
Section: Discussionmentioning
confidence: 65%
“…Although others have measured impact of publications using citation counts [24], we did not consider the four years of our study sufficient time for citations to accrue in a way that would reflect impact. We thus considered citation data to be a less reliable measure of research output.…”
Section: Methodsmentioning
confidence: 99%
“…Positive associations between international collaboration and citation rates have also been found for Scandinavian science (Glänzel, 2000), Brazilian science (Leta & Chaimovich, 2002), New Zealand science (Goldfinch, Dale, & DeRouen, 2003), and Danish industry (Frederiksen, 2004). In contrast, papers with at least one Harvard University co-author attract less citations the greater the physical distance between the affiliations (Lee, Brownstein, Mills, & Kohane, 2010), suggesting that international collaboration is ineffective for Harvard authors. This is probably a special case for one elite university and hence does not negate the other findings.…”
Section: : Citations and National Or International Collaborationmentioning
confidence: 96%
“…Authors who work physically close together also produce higher quality science. 13 In a study, authors separated by more than 1 km had the lowest number of citations. Groupthink is common in science, so common that author bylines keep getting longer.…”
mentioning
confidence: 98%